The Design and Development of a Digital Game for Young Children to Train Computational Thinking Skills Like a Programmer - Sungkaew, Kornchulee; Phophet , Chankrit; Yingmuang, Sompong; Kaewnamrung, Chayanon (Journal of Applied Statistics and Information Technology, 2023)
Control structures are fundamental concepts utilized by programmers across various programming languages. These structures enable programmers to think algorithmically, implementing decision-making processes and iterations for program conciseness and systematic functionality. The development of computational thinking skills is crucial in fostering logic and creativity, preparing individuals for the challenges of the twenty-first century. Recognizing the importance of instilling these skills from an early age, the incorporation of the three primary control structures—sequence, conditions/selections, and loops—into a digital game becomes a pertinent educational tool for young children. This research has two main objectives: first, to design and develop a digital game named "Hamster" that trains computational thinking skills akin to those used by programmers; second, to evaluate the game experience of children engaging with it. The methodology involves analyzing the computational thinking skills framework used by programmers and studying relevant content from textbooks and exercises used in primary school computational science subjects. The digital game, created using Scratch 3.0, underwent usability testing by experts. Subsequently, 95 children participated in the game experience evaluation. Results indicated that the game’s design and development align with the computational thinking skills framework, focusing on sequence, conditions/selections, and loops. The game’s difficulty level, user interaction ease, and graphical elements were deemed suitable for young children. In the evaluation of game experience, children expressed positive sentiments, finding the game easy to play and engaging. They exhibited a desire to progress through levels, maintaining interest without experiencing boredom. The mouse-controlled interface, clear instructions, comprehensible feedback, and user-friendly symbols contributed to the game’s accessibility, enhancing the overall experience for children.